Energetics of biomolecular shells in core–shell nanocomplexes - Kristina Lilova; Tamilarasan Subramani; Isabella Montini; Anne Harrison; Manuel Scharrer; Hongwu Xu; Alexandra Navrotsky (Proceedings of the National Academy of Sciences, 2026)
In this work, the stabilization enthalpy of patchy core–shell nanocomplexes is used to assess their thermodynamic stability. It is defined as the enthalpy of formation of a hydrated core–shell complex from hydrated (uncoated) core and hydrated shell species. Instead of the macroscopic bulk phase, the reference state is taken as the hydrated (uncoated) core of the nanocomplex with the same crystallite size. The stabilization enthalpies of three patchy magnetite (Fe 3 O 4 ) nanoparticles coated with three model biomolecules, bovine serum albumin, potato starch, and lauric acid were determined experimentally and the contributions of the primary hydration enthalpy and the adsorption of the biomolecules on the magnetite surface are measured and discussed. The findings establish the stabilization enthalpy as a quantitative basis to describe nanoparticle stability and interactions in biological and other complex media, which are crucial for biomedical applications.